Teaching Training in Physical Education, Towards a rationale for a Socio-constructivist Approach (Analytic Teaching, 1996)
Introduction:  In physical education, three dominant discourses in teacher training exist, namely pedagogy of performance, critical pedagogy and postmodern pedagogy. The pedagogy of performance (Siedentop, 1983, 1994) is traditional pedagogy. It finds its essence in techniques and strategies of practical application. It mostly involves questions which tend towards probable results. This paradigm is called scientific or positivist.